2021
DOI: 10.3390/risks9060119
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Non-Economic Variables Affecting Fraud in European Countries

Abstract: Fraud is one of the most harmful phenomena, because it leads to collapse of organizations, causes economic downfall of countries, and destroys faith in a country’s capital markets. The impact of fraud is complex and has varying degrees depending on political and financial institutional structures of a country. In this paper, we investigate the combined effect of economic and non-economic variables on fraud using a sample of 41 developed, in transition, and developing European countries. The data cover the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
(86 reference statements)
1
6
0
Order By: Relevance
“…Different factors, some of which are economic and others which are noneconomic (Ahmad et al. , 2021) determine corruption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Different factors, some of which are economic and others which are noneconomic (Ahmad et al. , 2021) determine corruption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Empirically, Salhi & Boujelbene (2012) have examined the relationship between internal governance mechanisms and risk-taking in the banking industry, and Ahmad et al (2021) found a significant relationship between business operational risk and fraud. Iminza et al (2015) have found a positive but weak relationship between governance and operational risk of fraud.…”
Section: Corporate Governance Operational Risk and Financial Statemen...mentioning
confidence: 99%
“…However, either pressure for higher profits and rising share prices or pressure to expropriate assets (for the benefit of the controlling shareholder and the manager's personal business interests) encourage top managers to engage in or approve of fraudulent activity as a means to fulfill this objective (Chen et al, 2006in Shi et al, 2017. Thus, financial statements that contain elements of fraud have an impact on decreasing the financial information integrity and become an invalid information source to be used as a basis for analysis in decision making by various parties, such as investors, creditors, employees, auditors, and competitors (Ansar, 2011) Determinants of fraud include economic and non-economic aspects (Ahmad et al, 2021). One of the identified variables that can influence fraud is operational risk in the economic literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each type of fraud has its own specific characteristics and therefore there are a number of factors that trigger fraud (Ahmad et al, 2021;Opreţ et al, 2017;Vondráček & Eibl, 2018). The primary reason for tax fraud is the conflict of interests between the private and public sectors.…”
Section: Introductionmentioning
confidence: 99%